Exploring the Kinetic and Thermodynamic Relationship of Charge Transfer Reactions Used in Localized Electrodeposition and Patterning in a Scanning Bipolar Cell - Braun, Trevor M.; Schwartz, Daniel T. (Frontiers in Chemistry, 2019)
Bipolar electrochemistry involves spatial separation and localization of charge balanced reduction and oxidation reactions on an electrically floating electrode, a result of intricate coupling of the work piece with the ohmic drop in the electrochemical cell and to the thermodynamics and kinetics of the respective bipolar reactions. When paired with a rastering microjet electrode, in a scanning bipolar cell (SBC), local electrodeposition and patterning of metals beneath the microjet can be realized without direct electrical connections to the workpiece. Here, we expand on prior research detailing electrolyte design guidelines for electrodeposition and patterning with the SBC, focusing on the relationship between kinetics and thermodynamics of the respective bipolar reactions. The kinetic reversibility or irreversibility of the desired deposition reaction influences the range of possible effective bipolar counter reactions. For kinetically irreversible deposition systems (i.e. nickel), a wider thermodynamic window is available for selection of the counter reaction. For kinetically reversible systems (i.e. copper or silver) that can be easily etched, tight thermodynamic windows with a small downhill driving force for spontaneous reduction are required to prevent metal patterns from electrochemical dissolution. Furthermore, additives used for the bipolar counter reaction can influence not only the kinetics of deposition, but also the morphology and microstructure of the deposit. Cyclic voltammetry measurements help elucidate secondary parasitic reduction reactions occurring during bipolar nickel deposition and describe the thermodynamic relationship of both irreversible and reversible bipolar couples. Finally, finite element method simulations explore the influence of bipolar electrode area on current efficiency and connect experimental observations of pattern etching to thermodynamic and kinetic relationships.